2004
DOI: 10.1007/bf02712113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypervitaminosis of vitamin B3 on silkworm biology

Abstract: A high-dose of vitamin B 3 in silkworm diet interrupts larval feeding and normal growth. High mortality of larvae occurs during molting and they cannot complete this process normally. Also the larvae exhibit nicotinamide hypervitaminosis symptoms such as immobility, dyspepsia, darkening of the skin, inability to excrete normally, exerting brownish fluid from anus and swelling of rectal muscles. Maximum larval weights in 1, 2 and 3 g/l treatments were 2⋅9, 1⋅6 and 1⋅2 g respectively, while maximum larval weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
3
11
0
1
Order By: Relevance
“…The hydrolysis of acid phosphatase (ACP) and alkaline phosphatase (ALP) phosphomonoesters under acid or alkaline conditions, respectively 25 . Alkaline phosphatase (ALP) is used as a membrane marker enzyme, active in intestinal epithelial cells, malpighian tubules and hemolymph of insects 25,57 . A decrease in ACP levels due to plant extract could be attributed to reduced phosphorous liberation for energy metabolism, decreased rate of metabolism as well as decreased rate of transport of metabolites 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of acid phosphatase (ACP) and alkaline phosphatase (ALP) phosphomonoesters under acid or alkaline conditions, respectively 25 . Alkaline phosphatase (ALP) is used as a membrane marker enzyme, active in intestinal epithelial cells, malpighian tubules and hemolymph of insects 25,57 . A decrease in ACP levels due to plant extract could be attributed to reduced phosphorous liberation for energy metabolism, decreased rate of metabolism as well as decreased rate of transport of metabolites 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…(Gacar and Tasksn, 2009). Alkaline phosphatase (ALP) is a brush border membrane marker enzyme and is especially active in tissues with active membrane transport, such as intestinal epithelial cells (Etebari and Matindoost, 2004a), Malpighian tubules (Etebari and Matindoost, 2004b) and hemolymph (Etebari et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Higher quantity of vitamin in diet has been reported to decrease the feeding of insects (Friend, 1958). Etebari and Matindoost (2004) observed that high dose of vitamin B 3 in the diet interrupt feeding and normal growth of silkworm larvae. The observed High mortality was recorded during molting of larvae.…”
Section: Discussionmentioning
confidence: 99%